ANALISIS KEBIJAKAN PENGELOLAAN PERKEBUNAN KELAPA SAWIT DI PROVINSI SUMATRA UTARA - Dina Meria Sinaga; Mulyo Hendarto (Universitas Diponegoro, 2012)
ABSTRACT This study aims to analyze the right palm oil plantation management policy for the local economy, with the objectives: (1) Knowing the problems and issues that happen today in the management of palm oil plantations in North Sumatra province. (2) Identify and analyze alternatives policy in the management of palm oil plantations in North Sumatra. (3) Establish strategies and the priority of the regulation to overcome the conflict of interest in palm oil plantations. The data used in this study is primary and secondary data, moreover this study uses analytical hierarchy process method (AHP). Analyses were performed on thirteen alternatives of management policy of palm oil obtained from interviews with key persons. Alternative policy is divided into four aspects: Ecological aspects, Social, Institutional, and Economic. All of these alternatives policy will be analyzed on four component keys of the respondents (persons, local communities, the owner / entrepreneur oil, and oil workers). The analysist shows that the most dominant policy strategy of most important by each respondent is a policy in the palm oil plantation management efforts. The policy of development and agro-processing of palm oil waste, establishing policy synergies and improve communication between government agencies and institutions legislative. The number of inconsistency ratio is <0.1, which means the results of these analyzes are consistent and acceptable.